Backbone (1)H, (13)C and (15)N resonance assignments of the extracellular domain of tissue factor - Boettcher, John M. (2010)
Backbone (1)H, (13)C and (15)N resonance assignments are presented for the extracellular domain of tissue factor. Tissue factor is the integral membrane protein that initiates blood coagulation through the formation an enzymatic complex with the plasma serine protease, factor VIIa.